Lost in transition? The persistence of dictatorship mayors - González, Felipe (2021)
We look at Chile’s transition to democracy in 1990 to study the persistence of authoritarian politics at the local level. Using new data on the universe of mayors appointed by the Pinochet dictatorship (1973-1990), and leveraging on the arbitrary election rules that characterized the first local election in 1992, we present two main findings. First, dictatorship mayors obtained a vote premium that is larger among the last wave of incumbents and appears partially explained by an increase in local spending. Second, dictatorship mayors who were democratically elected in 1992 brought votes for the parties that collaborated with the dictatorship in subsequent elections held in democracy. These results show that the body of politicians appointed by a dictatorship can contribute to the persistence of elites and institutions.